Encyclopaedia of Indian women through the ages - Jain, Simmi (Kalpaz Publications, 2003)
Women have witnessed acute socio-economic problems in male-dominated society in the annals of Indian sub-continent. However, they maintained their identity and consequently emerged as a useful partner in the household affairs. The theme has been comprehensively weaved into four volumes, viz., ancient, medieval and modern India with a thrust on freedom struggle for Swaraj. It has vividly described status of women during the phases of history; her rights and duties, standard of education, lives of Devadasi and widows, female slaves, divorce, remarriage system, the Muslim queens, participation of women in three major movements during Gandhian era, and their sacrifices, status of Dalit women, socio-economic regeneration, nuns in Kerala, women and family welfare, role in labour force and vision of Annie Besant. These volumes would be useful for social scientists, researchers and students in India and abroad. Contents:- Vol 1- Contents, Preface 7, Introduction 11, 1. Status in the Vedic Era 15, 2. The Mahabharata Women 43, 3. The Marriage System 51, Arranged Marriage in Dharamasastra •, Impersonation • Misrepresentation., 4. Marital Status 61, 5. Rights and Duties after Marriage 75, Polyandry • Mutual Rights and Duties of Husband, and Wife • Rights from the Ancient Times •, Foremost Duty., 6. The Initiation 93, Sacred Thread • Education., 7. Costumes 103, The Headdress • Meagre Evidence • Sewn Clothes, • Ornaments., 8. Sexual Life 123, 9. Motherhood and Widowhood 171, Widowhood • Epics Period., 10. Punarbhu: Her Social Status 191, Remarriage of Women • Remarriage When Husband, Unheard of • Remarriage of Widows • Divorce., 11. Foreign Accounts of Marital Arrangements 205, Niyoga, 12. Property Rights 237, Wife's Property Rights • Extent of Wife's Right, Over Strìdhana • Succession to Strìdhana •, 6 Encyclopaedia of Indian Women Through the Ages, Daughter's Property Rights • Daughters with, Brothers • Brotherless Daughters • Widow • Mother, • Grand Mother • General Conclusion